Prevalence and Characteristics of Social Withdrawal Tendency Among 3–24 Months in China: A Pilot Study - Zhou, Fengjuan; Huang, Peiyuan; Wei, Xueling; Guo, Yixin; Lu, Jinhua; Feng, Lanlan; Lu, Minshan; Liu, Xian; Tu, Si; Deprez, Alexandra; Guedeney, Antoine; Shen, Songying; et al. (Frontiers in Psychiatry, 2021)
Background: Sustained withdrawal behavior is an obstacle for child development. The present study aimed to preliminarily evaluate the prevalence of social withdrawal tendency in young Chinese children using the Alarm Distress Baby Scale (ADBB) and describe the characteristics of socially withdrawn children. Method: This was a cross-sectional analysis as part of a prospective cohort study. A total of 114 children aged 3-24 months were included. The following instruments were administered: the Chinese version of ADBB, the Ages and Stages Questionnaire (ASQ-3), the Ages and Stages Questionnaire: Social-Emotional (ASQ:SE), and the Infant Temperamental Questionnaire. The tendency of social withdrawal in children was assessed using the ADBB. Social withdrawal was defined as an ADBB score of 5 or above. Student’s t-test, χ2 test, and Fisher’s exact test were performed to identify the differences in maternal and child characteristics between the children with and without social withdrawal. Age-specific indicators of development in these two groups were also presented. Results: About 16.7% of the children were socially withdrawn. Compared with those without social withdrawal, children with social withdrawal were older and had higher proportions of boys (68.4% vs. 42.1%) and social-emotional development delay (63.2% vs. 0%). In age-specific analyses, social-emotional development was poorer in children with social withdrawal across all age groups from 3 to 24 months. Conclusion: Assessed by the ADBB, the prevalence of social withdrawal tendency in young Chinese children was similar to that reported in the European population; children with social withdrawal tended to have poorer social-emotional development. Further research with larger sample sizes is needed to validate the scale and confirm these findings.